An investigation of the use of linguistic probes "by" and "in order to" in assessing moral grammar. (2nd January 2016) - Watkins, Hanne M.; Laham, Simon M.
ABSTRACT: Proponents of the linguistic analogy suggest that methodologies originally developed for investigating linguistic grammar can also be fruitfully applied to the empirical study of moral grammar : the causal and intentional representations of moral events which – according to the linguistic analogy – drive moral judgements. In the current study, we put this claim to the empirical test. Participants were presented with moral dilemmas which previously have been shown to implement a central principle in moral judgements: the principle of double effect (PDE). Participants responded to by and in order to probes to assess causal and intentional representations of this principle. Results show that these linguistic probes do not relate to moral judgement in the manner predicted by proponents of the linguistic analogy and moral grammar. Although the linguistic analogy is a theoretically rich framework, the procedures posited to give it empirical traction require revision.